Evolutionary game model of information management mechanism for public opinion governance - Shuting LIU, Yinghua MA, Xiuzhen CHEN (网络与信息安全学报, 2023)
Conflicting information in online social networks, often stemming from opposing views, can lead to rumors and the fragmentation of society.A reputation-based dynamic information management mechanism was proposed, adopting a dynamic reward and punishment strategy to decrease unnecessary information conflict so as to activate self-purification of network.By utilizing evolutionary game theory, a cumulative-prospect-based evolutionary game model of social network information conflict was constructed to validate the efficacy of the proposed mechanism.Numerical simulations were conducted to analyze the evolutionary trends of 18 different theoretical application scenarios under 9 constraints.The results demonstrate that, under constraint 5, both sides of the game tend to exhibit relatively rational behavior towards conflicts.Furthermore, dynamic evolution analysis and sensitivity analysis of the model parameters were performed while satisfying constraint 5, providing practical strategic suggestions for the dynamic information management mechanism.This model represents a novel attempt to capture the interaction of multiple factors, such as interest-driven behavior and conformity psychology, in the evolution of public opinion.Moreover, the model successfully simulates well-known patterns of rumor dissemination, confirming its validity.The proposed model offers valuable insights for the development and design of malicious information control systems in social networks and provides new ideas for the research and implementation of public opinion governance.